Estimated rates of influenza‐associated outpatient visits during 2001‐2010 in 6 US integrated healthcare delivery organizations. Issue 1 (15th February 2018) - Zhou, Hong; Thompson, William W.; Belongia, Edward A.; Fowlkes, Ashley; Baxter, Roger; Jacobsen, Steven J.; Jackson, Michael L.; Glanz, Jason M.; Naleway, Allison L.; Ford, Derek C.; Weintraub, Eric; Shay, David K.
Abstract : Background: Population‐based estimates of influenza‐associated outpatient visits including both pandemic and interpandemic seasons are uncommon. Comparisons of such estimates with laboratory‐confirmed rates of outpatient influenza are rare. Objective: To estimate influenza‐associated outpatient visits in 6 US integrated healthcare delivery organizations enrolling 7.7 million persons. Methods: Using negative binomial regression methods, we modeled rates of influenza‐associated visits with ICD‐9‐CM‐coded pneumonia or acute respiratory outpatient visits during 2001‐10. These estimated counts were added to visits coded specifically for influenza to derive estimated rates. We compared these rates with those observed in 2 contemporaneous studies recording RT‐PCR‐confirmed influenza outpatient visits. Results: Outpatient rates estimated with pneumonia visits were 39 (95% confidence interval [CI], 30‐70) and 203 (95% CI, 180‐240) per 10 000 person‐years, respectively, for interpandemic and pandemic seasons. Corresponding rates estimated with respiratory visits were 185 (95% CI, 161‐255) and 542 (95% CI, 441‐823) per 10 000 person‐years. During the pandemic, children aged 2‐17 years had the largest increase in rates (when estimated with pneumonia visits, from 64 [95% CI, 50‐121] to 381 [95% CI, 366‐481]). Rates estimated with pneumonia visits were consistent with rates of RT‐PCR‐confirmed influenza visits during 4 of 5 seasons in 1 comparison study. In another, rates estimated with pneumonia visits during the pandemic for children and adults were consistent in timing, peak, and magnitude. Conclusions: Estimated rates of influenza‐associated outpatient visits were higher in children than adults during pre‐pandemic and pandemic seasons. Rates estimated with pneumonia visits plus influenza‐coded visits were similar to rates from studies using RT‐PCR‐confirmed influenza.